From existing conventional building towards LEED certified green building: case study in Bangladesh - Iqbal, Ashik; Jahan, Ismat; Wasiew, Qudrati Al; Emu, Imtiaz Ahmed; Chowdhury, Dipta (Frontiers in Built Environment, 2023)
Green Building refers to the planning, design, construction, and operation of buildings considering indoor environment quality, occupant health, using energy, water, and other resources more efficiently; and reducing waste, pollution, and the overall environmental impact. Among the Green Building guidelines, Leadership in Energy and Environmental Design (LEED) offers a certification and rating system by which buildings are certified in different categories. The LEED rating system is used to rate an existing building how much it is fulfilling the criteria of Green Building (GB) or not. This research explored how an existing conventional building can be retrofitted to satisfy green building standards. An academic building of KUET has been selected for the study. A field survey and Participatory Rural Appraisal (PRA) tools (i.e., Focus Group Discussion (FGD), Key Informant Interview (KII)) were used for the data collection and then the data was analyzed by comparative analysis concerning the LEED 2009 rating system for assessing the building. The New Academic building receives 31 points out of 110 and so cannot earn any certification level. The lacking for which the points were not gained is identified and the installation of water and energy efficiency features, rooftop gardening is suggested as retrofitting options to earn the green building certification level.